O Corpo Que Fala: Moralidade, Narrativas De Experiência E Micropolíticas De Resistência (PERcursos Linguísticos, 2020)
A relationship between narrative practices and agency / resistance is the central focus of this article, which is based on the theoretical and epistemological bases of Parallel Narrative Analysis to Critical Discourse Analysis. We take a look at oral narratives of vicious experiences in a very particular context: a lunch table between co-workers who act as lawyers in peripheral territory, with the aim of observing the place of the body in everyday linguistic practices in which resistance micropolitics are included. To do so, we rely on the performance concepts of narrative and identity (AUSTIN, [1962] 1990; BAUMAN, 1986; MISHLER, 2002; RIESSMAN, 2008; BASTOS, 2008; BUTLER, [1990] 2015), as well as studies on relations between narratives , body and identity (PINTO, 2007). We intend, therefore, to demonstrate that linguistic studies that deal with an articulation between narratives, body and identity must take into account an inevitable relationship between bodies and contexts, occupying them with their inscriptions located here and now and their emergencies in everyday interactional practices, evidence of gender and class marks.